2017
DOI: 10.1123/japa.2016-0219
|View full text |Cite
|
Sign up to set email alerts
|

High Volume Exercise Training in Older Athletes Influences Inflammatory and Redox Responses to Acute Exercise

Abstract: To examine whether the volume of previous exercise training in older athletes influences inflammatory, redox, and hormonal profiles, 40 trained marathon runners were divided into higher-volume (HVG, ∼480 min/week) and lower-volume groups (LVG, ∼240 min/week). Plasma inflammatory proteins, redox biomarkers, salivary testosterone, and cortisol were assessed at restand following two maximal acute exercise bouts. At rest, the LVG exhibited higher CRP, higher protein carbonyls, and lower SOD activity compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 75 publications
3
5
0
Order By: Relevance
“…However, we observed no relationships between self-reported physical activity levels and IL-6, IL-10, or TNF-α changes in response to exercise. These findings support previous observations in older individuals (Estrela et al, 2017 ). Estrela et al ( 2017 ) found no difference in the IL-6 or TNF-α response to two successive bouts of maximal exercise between marathon runners with higher (~480 min/week) and lower training volumes (~240 min/week) (Estrela et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, we observed no relationships between self-reported physical activity levels and IL-6, IL-10, or TNF-α changes in response to exercise. These findings support previous observations in older individuals (Estrela et al, 2017 ). Estrela et al ( 2017 ) found no difference in the IL-6 or TNF-α response to two successive bouts of maximal exercise between marathon runners with higher (~480 min/week) and lower training volumes (~240 min/week) (Estrela et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…These findings support previous observations in older individuals (Estrela et al, 2017 ). Estrela et al ( 2017 ) found no difference in the IL-6 or TNF-α response to two successive bouts of maximal exercise between marathon runners with higher (~480 min/week) and lower training volumes (~240 min/week) (Estrela et al, 2017 ). Taken together, the findings of the current study and those reported previously suggest that neither cardiorespiratory fitness nor physical activity levels alter the acute cytokine responses to exercise in healthy older adults, and these findings appear to be consistent following both maximal and submaximal exercise.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4,5 A reduction in the availability of carbohydrates for exercise stimulates the release of IL-6 as it can assist in the maintenance of serum glucose levels during exercise. 5 IL-6 is an important marker since an increase in its concentration is associated with an increase in the levels of acute-phase inflammatory proteins, such as C-reactive protein, 6 the risk of cardiovascular events, 7 and the process of rupture or erosion of atherogenic plaques. 8 Among men, IL-6 is associated with the risk of myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…9 The majority of studies reported in the literature on this theme evaluated session (bout) exercise or a long-distance test (marathon, half-marathon, or 164km of cycling) and showed an increase in the levels of IL-6 released into blood vessels. [6][7][8] However, chronic training could reduce the release of IL-6 by skeletal muscle because exercise improves the energy performance of the myocytes. 10 Maintaining IL-6 concentrations promotes homeostasis in the inflammatory response and better use of the energy framework without damaging the myocytes.…”
Section: Introductionmentioning
confidence: 99%